Angiosarcoma arising in association with vascular Dacron grafts and orthopedic joint prostheses: clinicopathologic, immunohistochemical, and molecular study - Agaimy, Abbas; Ben-Izhak, Ofer; Lorey, Thomas; Scharpf, Marcus; Rubin, Brian P. (Annals of Diagnostic Pathology, 2016)
Angiosarcoma may rarely arise near an inert foreign body material including vascular grafts and metal joint prostheses. Sixteen such cases have been reported since 1972 but mostly in the radiologic or surgical literature without detailed histologic or molecular analyses. We herein describe the clinicopathologic and molecular features of 2 new cases and reanalyzed 3 previously reported cases of angiosarcoma that developed in association with Dacron grafts for vascular repair (n=3) or related to orthopedic metal prostheses for joint replacement (n=2). All patients were men aged 50 to 84 years (median, 71 years). Mean time to development of angiosarcoma was 9years (range, 4.6-17 years). Symptoms were recurrent bleeding/loosening of prosthesis for suspected infection (in the joint prosthesis cases) and fatigue, weight loss, and abdominal symptoms in the Dacron-associated cases. Four patients died of disease within 1 to 24 months (mean, 8 months). One patient was alive after radical surgery, radiochemotherapy, and embolization of pulmonary metastases (17months). Histologically, all tumors were high-grade epithelioid neoplasms with a predominant solid growth pattern and variable vasoformation. All tumors expressed CD31, ERG, FLI-1, and variably pancytokeratin (diffuse in 3 cases), but none expressed D2-40, MDM2, or CDK4. Fluorescence in situ hybridization analysis revealed no MDM2 or CDK4 alterations. MYC was expressed in all cases, but only 1 case was MYC amplified by fluorescence in situ hybridization. Angiosarcomas are exceedingly rare fatal complications of long-standing metal and Dacron prostheses. Awareness of their morphology and frequent cytokeratin expression is necessary to avoid misdiagnosis as metastatic carcinoma. Limited awareness of their existence explains delayed clinical diagnosis in most of cases. Absence of MDM2/CDK4 alterations underlines their distinction from intimal-type sarcomas.
EVALuna2:6695